Current State of Carbohydrate Recognition and C-Type Lectin Receptors in Pneumocystis Innate Immunity - Kottom, Theodore J.; Carmona, Eva M.; Limper, Andrew H. (Frontiers in Immunology, 2021)
Pneumocystis jirovecii is one of the most common fungal pathogens in immunocompromised individuals. Pneumocystis jirovecii pneumonia (PJP) causes a significant host immune response that is driven greatly by the organism’s cell wall components including beta-glucans and major surface glycoprotein (Msg). These ligands interact with a number of C-type lectin receptors (CLRs) leading to downstream activation of proinflammatory signaling pathways. This minireview provides a brief overview summarizing known CLR/Pneumocystis interactions.